Närvärme med bioenergi i Västra Ämtervik - Forsberg, Erik (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
I want to look at the possibilities to start selling hot water from a small district heating plant with bioenergy. My reason for doing this project is to look at a new business opportunity for our farm. Our company have less work during the winter time compared to the spring and this project will give us more work during the winter. I also want to take as much material as possible for heating from our farm in order to increase the value of the products from the farm. The project is in a village near us, where we should support a school, a churh, a home for the aged, a kindergarten and a parish hall with heat. In my work I have compared two different alternatives with each other. The first alternative is to put a central heater in one of the buildings, the home for the aged, in which we will burn oat. At the outside of the house we vill put a silo to store the oats in. We can fill the silo with machineries that we have on the farm. We will also save one of the old heaters in the building as a reserv and for max heating. The other houses will in this case continue with the same heating as today. The second alternative is to build a small district heating plant for all of the five buildings which we vill heat with wood chips. I thought that it would be interesting to compare there two alternatives because it vill be a pretty long culvertsystem for all this buildings and therefore see how that vill affect the economy. I found that it will be best economy to build the second alternative, although that will need a larger investment in a big culvertsystem. This alternative can produce heat to a price of 0,54 SEK/kWh. The other alternative produces heat to a price of 0,655 SEK/kWh.The main reason why the wood chips alternative was cheaper on producing kWh compared to the oat alternative is that oats costs almost twice as much as wood chips. Wood chips have been used for heating during a long time and the technology is well known and has a big reliability. To burn oats is a pretty new technology, one problem that can come in the future is how buildings nearby with metall roof will be affected from the smoke that has a pH as low as 2,1.